Hegemony in international society - Clark, Ian, 1949- (Oxford : Oxford University Press, 2011)
A major re-thinking of the concept of hegemony in international relations. On the basis of historical examples, Ian Clark presents an innovative scheme for rethinking hegemony, and applies it to the U.S. role in international organizations, in East Asia, and in the policy on climate change.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Hegemony; International relations